The legal framework governing International trade in services - salima REKIBA (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The General Agreement on Trade in Services, which came into force on 1 January 1995 with the creation of the World Trade Organization, applies to government measures affecting services provided on a commercial basis.